Relationship breakups - Collin, Jerome (Centre for Language Studies, Universiti Malaysia Sarawak, 2012)
Breaking up a relationship is not easy. Those on the verge of breaking up with their spouses may use different verbal and non-verbal means to express their desire to end the relationship. The following poems attempt to tell the complex processes of, and the mediums used for, relationship breakups.